Bipolar resistive switching in Ag/VO2(B)/SiOx/n++Si RRAM. (1st March 2022) - Li, Jiaping; Zhou, Xin; Xu, Liu; Wang, Jiale; Wu, Binhe; Wang, Chunrui
Abstract: Non-volatile resistive random-access memory (RRAM) is being promoted as a possible alternative to flash memory, however the optimal material system and sophisticated fabrication techniques hinder its utilization in practical routes. Here, we demonstrate the direct fabrication of metal/oxides/semiconductor (MOS) structured Ag/VO2 (B)/SiOx /n ++ Si RRAM via drop-coating process, in which bipolar resistive switching behavior was obtained and investigated systematically. The RRAM devices exhibit good cycle-to-cycle endurance (>30 cycles) and high on/off ratio (>60). The switching mechanism is proposed to form Ag conducting filaments via VO2 (B) nanorods' guide by comparing the resistive switching behavior of Ag/SiOx /n ++ Si, Ag/VO2 (B)/n ++ Si, Ag/VO2 (B)/SiOx /n ++ Si devices and the corresponding SEM images before and after the application of electric field, which is confirmed by introducing NaCl barrier layer in Ag/VO2 (B)-NaCl/SiOx /n ++ Si devices. The present study may pave a convenient route for fabricating the ultrahigh density resistive memory devices without the aid of complex fabrication techniques, as well as provide a new potential material system for RRAM.